Seasonal variation of zooplankton assemblages and their responses to water chemistry and microcystin content in shallow lakes in Thailand - Prasertphon, Rawipa; Chaichana, Ratcha; Jitchum, Pailin (Archives of Biological Sciences, 2023)
Paper description: Urban shallow lakes are exposed to eutrophication. Research on the density and variation of zooplankton in hypereutrophic lakes in tropical countries is limited. Zooplankton and its relationship with environmental variables were examined in shallow lakes in Thailand. We identified four groups of zooplankton, of which Rotifera was the most abundant group, followed by Copepoda, Protozoa, and Cladocera. Zooplankton assemblages were influenced by seasons and environmental variables. The content of microcystin has an adverse impact on Protozoa. This research improves the understanding of zooplankton assemblages in urban shallow lakes and their response to water quality. Abstract: This study examines zooplankton assemblage structure and density from five hypereutrophic urban shallow lakes between cool and hot periods in 2018-2019. We analyzed the variation of zooplankton and their relationship with environmental factors. Samples of zooplankton were collected from shallow lakes in different regions of Thailand. Four groups of zooplankton were identified, of which Rotifera was the most abundant group, followed by Copepoda, Protozoa, and Cladocera. Zooplankton assemblages were influenced by seasons, as indicated by multidimensional scaling analysis. The number of species and density of zooplankton were lower during the cool period than during the hot period. The increased density of zooplankton in the hot period may have been due to increased phytoplankton density as food sources. Pearson’s correlation coefficient revealed that Rotifera and Copepoda positively correlated with the temperature and pH, and Rotifera was negatively correlated with total phosphorus; a negative correlation was also observed between Protozoa and dissolved oxygen. The microcystin content tended to have a negative impact on specific small species such as Protozoa (Coleps sp.). Information from this research is important for further study involving factors affecting the size structure of zooplankton communities, especially large-bodied species in tropical regions.